Iron Deficiency Anemia and Dental Caries: A Systematic Review and Meta-Analysis - Rubén Aguirre-Ipenza DDS; Wendy Nieto-Gutiérrez MSc; Winnie Contreras DVM; Pavel J. Contreras MSc; Walter H. Curioso PhD (SAGE Publishing, 2024)
Objective. To evaluate the evidence regarding the association between iron deficiency anemia (IDA) and dental caries in children and adolescents. Methods. Searches were conducted in 4 international databases from the beginning of records until October 2023. Studies evaluating the association between IDA and dental caries in individuals aged 6 months to 18 years were included. Risk of bias was assessed using the Newcastle Ottawa Scale. Quantitative synthesis was performed using the inverse variance or Mantel-Haenzel method, depending on the type of outcome analyzed. Measures of association included odds ratios and mean differences, employing a random-effects model with a 95% confidence interval. Results. A total of 1161 studies were identified, of which 12 were selected for qualitative review and 9 for meta-analysis. A significant association was found between IDA and dental caries (odds ratio of 3.54; 95% CI: 2.54-4.94) and a higher rate of dental caries in the presence of IDA (mean difference of 1.96; 95% CI: 1.07-2.85). The certainty of evidence according to GRADE was rated as very low. Conclusions. Despite the limited certainty, the findings indicate a significant association between IDA and dental caries. It is prudent to interpret these results with caution, considering the methodological limitations of the studies. However, given the potential relevance of this association for public health, recommending oral health strategies, including preventive and corrective dental interventions, for anemia control programs underlines the importance of more rigorous future research to strengthen the certainty of the evidence and guide the implementation of these strategies.